ANALYSIS OF HYPER-HYPONYMIC TERMS RELATED TO COUNTRY STUDIES IN ENGLISH AND UZBEK LANGUAGES (The Conference Hub, 2025)
This article analyzes and explains the terms hyper-hyponymy in national studies through examples.